Sub-cultural differences in cognitive development among elementary students in Trinidad and Tobago - Fraser-Abder, Pamela (My University, 1986)
There is need to conduct more Piagetian research in the Caribbean in order to develop a basis for a culturally appropriate curriculum. This article analyses the performance of primary school students in Trinidad and Tobago on a single class task. The sample comprised 6,686 students representing 3 percent of the primary school population, randomly selected from the various school types, localities, and cultural, social, and racial backgrounds. Five areas were investigated: gender, age, school administration, school type and socio-economic level. The results showed that: 1) females tended to achieve a higher concept developmental level than males, 2) the majority of students did not confirm to the Piagetian age: stage relationship, 3) children at private schools tended to achieve better than those at denominational and government schools, 4) males and females in all-male and all-female schools tended achieve better than males and females in co-educational schools, and 5) children of university graduates achieved better that those whose parents had received only or less than elementary education.
Keywords: Cognitive development